Abundance of low-temperature axial venting at the equatorial East Pacific Rise. (January 2021) - Chen, Sheng; Tao, Chunhui; German, Christopher R.
Abstract: Since their first discovery, predictions of the incidence of high temperature submarine vents has been made from along-axis surveys for the presence or absence of particle-rich "black smoker" hydrothermal plumes in the overlying water column. Recent work along intermediate and fast spreading ridges, however, has shown that abundant lower-temperature forms of seafloor fluid flow might be overlooked by this approach. Here, we report new data that allow us to test for both high- and low-temperature venting along the fast-spreading (110–132 mm/yr) equatorial East Pacific Rise (EPR), between 1.9°N and 4.9°S. We identify at least 32 discrete sites of hydrothermal activity, of which just 11 would have been resolved by particle-plume only survey methods. Such an approach would lead to a predicted frequency of high-temperature venting (Fs ) along this section of the EPR of 4.2 sites/100 km, consistent with other particle-plume only surveys conducted under the auspices of InterRidge . When we include ORP sensor data to prospect for near-seafloor evidence of low-temperature venting, however, the calculated spatial frequency (Fs) for all styles of seafloor fluid flow increases by more than 3-fold, to Fs ≥ 15.5 sites/100 km. Hence, this study provides confirmation that low-temperature venting should be widespread along all fast-spreading mid-ocean ridges. While an appreciation of the importance of low-temperature axial venting to geophysical fluxes (heat, mass) is well established, our results reveal evidence for low-temperature fluid flow that is out of geochemical (redox) equilibrium with the overlying water column. Consequently, these fluxes may also play an important but previously overlooked role in global-scale ocean biogeochemical cycles. Highlights: We investigated the fast-spreading EPR for the abundance of low-T submarine venting. Including low-T flow increases the incidence of venting by > 3-fold. Such low-T flow may play an important role in global-scale ocean biogeochemistry.